New Teachers’ Perceptions of Induction: Insights Into Principled Practices - Cherubini, Lorenzo (Alberta Journal of Educational Research, 2010)
Successfully inducting new teachers creates professional alliances to sustain learning organizational cultures. This research involved 30 beginning teachers from a large school board in southern Ontario. The theoretical frame of the study consists of a mixed qualitative data analysis methodology of grounded theory and discourse analysis. The findings elaborate on the value of induction programs that are modeled on individual differentiation according to teachers’ unique capacities. The new teachers who benefited most from their induction were those who were part of school cultures that integrated their professional development in meaningful endeavors. New teachers readily shared their self-declared accomplishments in induction experiences wherein they resolved their dilemmas through critical reflection and professional collaboration.